Implementation of MyWebAR Augmented Reality with a Scientific Approach to Improve Students’ Conceptual Understanding of Space Material - Firdaus, Thoha; G.A, Begimbetova; Sinensis, Arini Rosa; Widayanti, Widayanti; Yani, Deah Sadila Putri (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates the implementation of MyWebAR-based Augmented Reality (AR) integrated with a scientific approach in junior high school science learning and examines its impact on students’ conceptual understanding of Space (Astronomy) material. A quantitative quasi-experimental design with a one-group pretest–posttest model was employed with a sample of 33 seventh-grade students (Class VII D) at SMP Negeri 1 Belitang III, South Sumatra, Indonesia. Data were collected using validated essay instruments (Cronbach’s α = 0.866), observation sheets, and questionnaires. Students accessed three-dimensional planet models by scanning QR barcodes embedded in modified teaching modules, which activated AR visualizations through the mywebar.com platform. Data analysis using the normalized gain (N-Gain) index and Cohen’s d effect size was performed via the Jamovi software. Results demonstrate a substantial increase in mean scores from 26.27 (pretest) to 93.88 (posttest), yielding an N-Gain score of 0.92 (high category) and a Cohen’s d effect size of 1.26, indicating a very strong practical significance. Students exhibited heightened engagement and motivation throughout the AR-mediated learning sessions. These findings suggest that the integration of MyWebAR technology with a structured scientific approach constitutes a highly effective pedagogical strategy for enhancing conceptual understanding of abstract astronomical concepts at the junior secondary level. The findings also highlight the feasibility of web-based AR as an accessible alternative to application-dependent immersive learning media. Future studies should employ larger and more diverse samples, as well as comparison groups, to confirm the sustainability and generalizability of these learning outcomes.